Production of Rice in Nigeria: The Role of Indian-Nigerian Bilateral Cooperation in Food Security - I. U. Lucky (Vestnik MGIMO-Universiteta)
The article focuses on the impact of India-Nigeria agricultural cooperation on rice production in Nigeria. Since 2000 in the quest for food sufficiency, diversification of the country’s sources of foreign exchange, increasing employment for the rising population as well as expanding its external relations Nigeria has signed several bilateral agreements on agriculture with India. The analysis of the developments in the sub-sector, as well as media, governmental and non-governmental reports in the field and the interviews of the farmers has revealed that the Indian firms, including “Olam Group” and “Popular Farms and Mills Ltd”, have cultivated thousands of hectares of land, built mills and machinery, provided farmers in 16 Nigerian states with better rice seedlings, and engaged thousands of farmers in regular training improving employment and revitalizing communities in the country. The support given by the Indian firms has triggered an unprecedented increase in rice production. The paper concludes that the agreements, particularly the one of 2017, have further promoted, strengthened and expanded rice production in the context of food security, job creation and saving foreign exchange. The article, therefore, demonstrates how Nigeria-India bilateral ties and cooperative programs have changed the dynamics of rice production in the country and brought more profound economic consequences. Despite the fact that Nigeria is not yet selfsufficient in rice production with the gap of around 2.5 million tonnes, the agricultural programs initiated within the framework of the Nigeria-India bilateral agreements and realized as large-scale agriculture programmes including investments, training, supply of better seedlings, land cultivation promoted by powerful corporations have significantly changed the economic and social environment in Nigeria.